Behavioral economics in companies: Nudging green behavior. Evidence of the effectiveness of green nudges in companies - Dominik Enste; Jennifer Potthoff (Institut der deutschen Wirtschaft (IW), 2023)
Climate protection is one of the greatest challenges society and economy are currently facing. In addition to policy (Macro level) and individual consumers (Micro level) also companies (Meso level) are confronted with increasing pressure to act more ecologically sustainable. Besides ecological improvement in the production processes and value chains, corporate transformation to more ecological sustainability also demands a development towards the office model of the future, the "Green Office" which is realized by the triade of "green IT", "green building" and "green behavior". This requires employees who are willing to change and structures who enable change. In view of the fact that employees in offices are not yet financially incentivized to act ecologically sustainable in the work context the question arises as to whether behavioral-economic insights can be used to motivate employees towards more ecological choices in their work life. By an intelligent and effective use of green nudges employees can be supported by adopting climate-friendly choices with regard to the following fields of action: energy efficiency, sustainable mobility and resource use. Exemplary nudges are gamification elements such as team bicycle or energy-saving competitions, feedback on electricity or fuel consumption, carpool simplifications and default changes such as double-sided printing. If properly designed, green nudges can combine corporate climate protection, fun, team spirit and freedom of choice and can, for instance, achieve significant savings of 6.5 percent in electricity consumption. If all offices used in the top 7 cities (Cologne, Düsseldorf, Stuttgart, Frankfurt, Hamburg, Munich, Berlin) would save an average of 6.5 percent electricity through green nudges, assuming an annual electricity consumption of 70kWh per m2 office area, 419,676 MWh, more than 176,000 tons of CO2 and 167.87 million euros in electricity costs could be yearly saved in Germany. – – Der Klimaschutz ist eine der größten Herausforderungen, vor denen Gesellschaft und Wirtschaft derzeit stehen. Neben der Politik (Makroebene) und den einzelnen Verbrauchern (Mikroebene) sind auch Unternehmen (Mesoebene) mit zunehmendem Druck konfrontiert, ökologisch nachhaltiger zu handeln. Die unternehmerische Transformation zu mehr ökologischer Nachhaltigkeit erfordert neben der ökologischen Verbesserung in den Produktionsprozessen und Wertschöpfungsketten auch eine Entwicklung hin zum Büromodell der Zukunft, dem "Green office", das durch den Dreiklang von "Green IT", "Green building" und "Green behavior" realisiert wird. Dies erfordert veränderungsbereite Mitarbeiter und Strukturen, die den Wandel ermöglichen. In Anbetracht der Tatsache, dass Mitarbeiter in Büros noch keine finanziellen Anreize haben, sich im Arbeitskontext ökologisch nachhaltig zu verhalten, stellt sich die Frage, ob verhaltensökonomische Erkenntnisse genutzt werden können, um Mitarbeiter zu ökologischeren Entscheidungen in ihrem Arbeitsleben zu motivieren. Durch einen intelligenten und effektiven Einsatz von Green Nudges können Mitarbeiter dabei unterstützt werden, klimafreundliche Entscheidungen in folgenden Handlungsfeldern zu treffen: Energieeffizienz, nachhaltige Mobilität und Ressourcennutzung. Beispielhafte Nudges sind Gamification-Elemente wie Team-Fahrrad- oder Energiesparwettbewerbe, Feedback-Mechanismen zum Strom- oder Kraftstoffverbrauch, Vereinfachungen von Fahrgemeinschaften, und Default-Änderungen wie zum Beispiel doppelseitiges Drucken. Richtig konzipiert können Green Nudges betrieblichen Klimaschutz, Spaß, Teamgeist und Entscheidungsfreiheit miteinander verbinden und beispielsweise signifikante Einsparungen von 6,5 Prozent beim Stromverbrauch erzielen. Wenn alle Büros der deutschen Top-7 Städte (Köln, Düsseldorf, Stuttgart, Frankfurt, Hamburg, München, Berlin) durch Green Nudges durchschnittlich 6,5 Prozent Strom einsparen würden und man von einem jährlichen Stromverbrauch von 70kWh pro m2 Bürofläche ausgeht, könnten in Deutschland jährlich 419.676 MWh, mehr als 176.000 Tonnen CO2 und 167,87 Millionen Euro Stromkosteneingespart werden.
Keywords: D22; D91; Q51; 330; environmental awareness; sustainability; nudging; company; Germany; Umweltbewusstsein; Nachhaltigkeit; Nudge; Unternehmen; Deutschland